Quality indicators for the diagnosis and management of chronic rhinosinusitis. Issue 12 (12th July 2018) - Cottrell, Justin; Yip, Jonathan; Chan, Yvonne; Chin, Christopher J.; Damji, Ali; de Almeida, John R.; Desrosiers, Martin; Janjua, Arif; Kilty, Shaun; Lee, John M.; Macdonald, Kristian I.; Meen, Eric K.; et al.
Abstract : Background: Chronic rhinosinusitis (CRS) has been identified as a high‐priority disease category for quality improvement. To this end, this study aimed to develop CRS‐specific quality indicators (QIs) to evaluate diagnosis and management that relieves patient discomfort, improves quality of life, and prevents complications. Methods: A guideline‐based approach, proposed in 2012 by Kötter et al. was used to develop QIs for CRS. Candidate indicators (CIs) were extracted from 3 practice guidelines and 1 international consensus statement on the diagnosis and management of CRS. Guidelines were evaluated using the Appraisal of Guidelines for Research and Evaluation II (AGREE II) tool. Each CI and its supporting evidence was summarized and reviewed by an expert panel based on validity, reliability, and feasibility of measurement. Final QIs were selected from CIs utilizing the modified RAND Corporation–University of California, Los Angeles (RAND/UCLA) appropriateness methodology. Results: Thirty‐nine CIs were identified after literature review and evaluated by our panel. Of these, 9 CIs reached consensus as being appropriate QIs, with 4 requiring additional discussion. After a second round of evaluations, the panel selected 9 QIs as appropriate measures of high‐quality care. Conclusion: This study proposes 9 QIs for the diagnosis and management of patients with CRS. These QIs can serve multiple purposes, including documenting the quality of care; comparing institutions and providers; prioritizing quality improvement initiatives; supporting accountability, regulation, and accreditation; and determining pay‐for‐performance initiatives.